Genesis of "Solitary Cations" Induced by Atomic Hydrogen. (27th July 2015) - Pettinari, Giorgio; Filippone, Francesco; Polimeni, Antonio; Mattioli, Giuseppe; Patanè, Amalia; Lebedev, Vladim; Capizzi, Mario; Amore Bonapasta, Aldo
Abstract : Substitution of constituent atoms and/or changes of crystal structure are routinely used to tailor the fundamental properties of a semiconductor. Here, it is shown that such a tailoring can also be realized thanks to a novel hydrogen effect. Four hydrogen atoms can screen the effect the crystal potential has on a constituent cation, thus generating a solitary cation : an effectively isolated impurity, so chemically different from the unscreened constituent cations that it strongly perturbs the electronic properties of the material by increasing its fundamental band‐gap energy. Such a hydrogen‐induced screening effect is removed by thermal treatments, thus permitting reversible modifications of both the "crystal chemistry" and material's properties. This phenomenon, observed in InN and other topical nitrides, should permit the development of a new class of materials as well as the fabrication of photonic devices and optical integrated circuits with distinct, tailor‐made regions emitting or absorbing light, all integrated onto a monolithic semiconductor structure. Abstract : Fundamental properties of nitrides are changed through deep modifications of the chemistry of their constituent atoms induced by atomic hydrogen. In InN, for example, an In cation is isolated from its crystalline environment by the cooperative action of four hydrogen atoms that locally screen the crystal potential, thus generating a " solitary cation " (In*) that remarkably increases the InN fundamental band‐gap energy.